PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PERILAKU AGRESIF SISWA SMKN 4 PEKANBARU - Silvia Ulfa; Elni Yakub; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effects of self management techniques in reducing the aggressive behaviour of students in SMKN 4 Pekanbaru. The quantitative research method was used in this study and the research was designed based on the one-group pretest – posttest design. The measuring instrument used in this study was the aggressive behavioural measurement scale consisting of 50 and 35 items before and after validation respectively. The validity score was calculated to be 0.396 and the reliability score was obtained as 0.948. The subject was determined by using purposive sampling technique, and it was obtained that 7 students in SMK 4 Pekanbaru were identified as having a high level of aggressive behaviour. The data were analysed by using the non-parametric statistical technique and were tested by using the Wilcoxon analysis test. This is known from